A novel receptor‐like kinase involved in fungal pathogen defence in Arabidopsis thaliana. Issue 7 (25th April 2018) - Ray, Justin; Yang, Xin; Kong, Feng; Guo, Tingwei; Deng, Fengyan; Clough, Steven; Ramonell, Katrina
Abstract: Plants are under constant attack from a variety of disease‐causing organisms. Lacking an adaptive immune system, plants repel pathogen attack via an array of pathogen recognition machinery. Receptor‐like kinases (RLKs) are involved in the recognition of pathogen‐associated molecular patterns (PAMPs) and activate resistance pathways against broad classes of pathogens. We have identified powdery mildew‐resistant kinase 1, an Arabidopsis gene encoding an RLK that is highly induced by chitin at early time points and localizes to the plasma membrane. Knockout mutants in pmrk1 are more susceptible to both Golovinomyces cichoracearum and Plectosphaerella cucumerina . Our data show that PMRK1 is essential in early stages of defence against fungi and provide evidence that PMRK1 may be unique to chitin‐induced signalling pathways. The results of this study indicate that PMRK1 is a critical component of plant innate immunity against fungal pathogens.